Case Report: Lower Limb Muscle Weakness in a Child With Kawasaki Disease - Huang, Lilin; Peng, Shumei; Li, Jing; Xie, Danyu (Frontiers in Pediatrics, 2022)
Kawasaki disease (KD) is a systemic vasculitis that may impact multiple organ systems in children. Myositis is an unusual presentation of KD that presents with muscle weakness. To date, a few pediatric patients with KD and myositis have been reported. Diffuse muscle weakness involving the 4 limbs was the most common presentation in these children. However, isolated lower limb involvement was rarely reported before. Here, we report lower limb muscle weakness in an 18-month-old child with KD. He presented with fever, rash, conjunctival injection, peeling over fingers and toes, and progressive muscle weakness of the lower limbs. Muscle enzymes were normal, but electromyography indicated myositis. The symptom of fever was relieved quickly by intravenous immunoglobulin and aspirin, which were ineffective for myositis. However, lower limb muscle weakness fully recovered 5 days after prednisolone treatment. This rare case might add value to the growing literature exploring the association of KD with myositis.